2018
DOI: 10.1002/adfm.201704919
|View full text |Cite
|
Sign up to set email alerts
|

Polydimethylsiloxane Composites for Optical Ultrasound Generation and Multimodality Imaging

Abstract: Polydimethylsiloxane (PDMS) is widely used in biomedical science and can form composites that have broad applicability. One promising application where PDMS composites offer several advantages is optical ultrasound generation via the photoacoustic effect. Here, methods to create these PDMS composites are reviewed and classified. It is highlighted how the composites can be applied to a range of substrates, from micrometer‐scale, temperature‐sensitive optical fibers to centimeter‐scale curved and planar surfaces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
173
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

6
4

Authors

Journals

citations
Cited by 102 publications
(175 citation statements)
references
References 109 publications
2
173
0
Order By: Relevance
“…Recently, an all-optical alternative to electronic ultrasound transducers has been presented that uses light to both transmit and receive ultrasound. Using fibre optic technology, optical ultrasound sources [3][4][5][6][7][8] and detectors [9][10][11][12][13][14] are readily miniaturised, exhibit high bandwidths and sensitivities, and are immune to electromagnetic interference. Recently, a benchtop system has been demonstrated that used a single fibre optic ultrasound detector and a centimetre-scale monolithic photoacoustic ultrasound generator membrane to achieve video-rate two-dimensional imaging [15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an all-optical alternative to electronic ultrasound transducers has been presented that uses light to both transmit and receive ultrasound. Using fibre optic technology, optical ultrasound sources [3][4][5][6][7][8] and detectors [9][10][11][12][13][14] are readily miniaturised, exhibit high bandwidths and sensitivities, and are immune to electromagnetic interference. Recently, a benchtop system has been demonstrated that used a single fibre optic ultrasound detector and a centimetre-scale monolithic photoacoustic ultrasound generator membrane to achieve video-rate two-dimensional imaging [15].…”
Section: Introductionmentioning
confidence: 99%
“…One advantage of the OpUS modality is the ability to integrate complementary modalities by tailoring the optical absorption profile of the ultrasound generating surface. 15 Previously this has been used to demonstrate co-registered ultrasound and photoacoustic imaging, but could be easily tailored to provide laser ablation through the same optical fibre as ultrasound generation.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, there is a significant progress in high‐resolution imaging based on photoacoustic transmitters. Two recent review articles cover high‐resolution imaging …”
Section: Photoacoustic Transmitters For Novel Applicationsmentioning
confidence: 99%